3D‐printed biosensor with poly(dimethylsiloxane) reservoir for magnetic separation and quantum dots‐based immunolabeling of metallothionein. Issue 11 (18th May 2015) - Heger, Zbynek; Zitka, Jan; Cernei, Natalia; Krizkova, Sona; Sztalmachova, Marketa; Kopel, Pavel; Masarik, Michal; Hodek, Petr; Zitka, Ondrej; Adam, Vojtech; Kizek, Rene
Abstract : Currently, metallothioneins (MTs) are extensively investigated as the molecular biomarkers and the significant positive association of the MT amount was observed in tumorous versus healthy tissue of various types of malignant tumors, including head and neck cancer. Thus, we proposed a biosensor with fluorescence detection, comprising paramagnetic nanoparticles (nanomaghemite core with gold nanoparticles containing shell) for the magnetic separation of MT, based on affinity of its sulfhydryl groups toward gold. Biosensor was crafted from PDMS combined with technology of 3D printing and contained reservoir with volume of 50 μL linked to input (sample/detection components and washing/immunobuffer) and output (waste). For the immunolabeling of immobilized MT anti‐MT antibodies conjugated to CdTe quantum dots through synthetic heptapeptide were employed. After optimization of fundamental conditions of the immunolabeling (120 min, 20°C, and 1250 rpm) we performed it on a surface of paramagnetic nanoparticles in the biosensor reservoir, with evaluation of fluorescence of quantum dots (λexc 400 nm, and λem 555 nm). The developed biosensor was applied for quantification of MT in cell lines derived from spinocellular carcinoma (cell line 122P‐N) and fibroblasts (122P‐F) and levels of the biomarker were found to be about 90 nM in tumor cells and 37 nM in fibroblasts. The proposed system is able to work with low volumes (< 100 μL), with low acquisition costs and high portability.